(untitled) (Research, Society and Development, 2021)
The objective of this work was to carry out a market research on the consumption of Munguba paçoca (Pachira aquatica Aubl.), In addition to elaborating formulations varying the addition of animal fat and evaluating sensorially. To prepare the paçoca, the Munguba seeds were dried in a conventional oven and crushed in a multiprocessor. In this study, the percentage of butter varied, with treatment 1 (T1) without addition, treatment 2 (T2) with 2.83% and treatment 3 (T3) with addition of 5.65%. Market research was carried out on Peanut and Munguba Paçoca (Pachira aquatica Aubl.). The sensory analysis was performed in a virtual way, and the acceptance test for the color and appearance attributes was used, with untrained judges, the preference ordering test and a search for the ideal product, in the three treatments and in the commercial sample of peanut. In the market research it was possible to notice that the Munguba paçoca would have adherence to the market. The acceptance test in relation to color and appearance had mean scores between 5 and 7, while the commercial was between 8 and 9. Regarding the comparison of the ideal paçoca and the evaluations given to the Paçocas de Munguba respectively in the item color, it had good acceptability in relation to texture apparent and granulometry apparent, further studies should be carried out. It is concluded that it is possible to prepare paçoca do Munguba (Pachira aquatica Aubl.), However it is necessary to improve the texture and conduct sensory tests of taste, texture and odor, as only visual analyzes were performed.